Educación financiera y toma de decisiones personales en estudiantes de contabilidad de la UNAP filial Requena año 2022 - Isuiza Soria de Gaviria, Rocio Antonia (2023)
In the thesis the general objective is evidenced: to determine the relationship between financial education and personal decision making in accounting students of the UNAP Filial Requena year 2022, being a descriptive-correlational research with a non-experimental design, where a population of 38 students, to whom the survey technique and the instrument as a questionnaire were applied in order to obtain information. concluding that financial education is within the very high level (26%) because they always make a personal income budget; just as they always have the habit of saving their money to pay for their education, health and food; but almost always students have knowledge about investment in business, companies, real estate and stock market; however, they never had difficulty applying for a bank loan. Regarding personal decision-making, it has been developing adequately (34%) since they always select alternatives to make the best decision; and they almost always consider that the experience provides the necessary information to solve a problem in the future. Finally, it was determined that there is a significant difference between financial education and personal decision-making, contrasted by (r=0.705; p=0.000) being considerable positive.